Evaluación del sistema de comunicación de posgrados de la Universidad Técnica de Cotopaxi como parte de la gestión institucional. Creación de un órgano de difusión de posgrados. - Medina Matute, Víctor Hugo (2014)
At the present time becomes important the popularization of science and university he has an important role to play through three binding symbiotic aspects of science, technology and innovation: teaching, production (scientific research) and dissemination. However, even in most universities, these activities are insufficient to the extent that research and science popularization tasks are not first order are latent limitations and deficiencies in the dissemination to the scientific community and are lacking in the university, specialized media in this labor, therefore that universities and in this case, the UTC must be directed to the creation of conditions aimed at the mass dissemination of the scientific and main results achieved through mostly print media , as in the case of scientific journals . In this sense, this research has a significant importance to the extent that fundamental purpose, the design and implementation of a scientific journal for the Directorate of Graduate Studies of the UTC as a means of dissemination and communication of scientific production especially the Grandee ongoing and graduates and graduates, which would constitute a means for them to publish and indexing projections. For support of the proposal, we applied a previously validated instrument, which responded to the indicators of the variables under study and assess the feasibility allowing design of the magazine. For the analysis and interpretation of results, we used the principles and parameters of descriptive statistics also underpin the proposal, on the theoretical foundations established methodologies concerning the creation of academic journals and in the criteria for organizations such as UNESCO, on the conceptions define current academic print journals. .